Effects of CYP2C19 Loss-of-Function Variants on the Eradication of H. pylori Infection in Patients Treated with Proton Pump Inhibitor-Based Triple Therapy Regimens: A Meta-Analysis of Randomized Clinical Trials - Tang, Hui-Lin; Li, Yan; Hu, Yong-Fang; Xie, Hong-Guang; Zhai, Suo-Di (PLOS ONE, 2013)
Background There are inconsistent conclusions about whether CYP2C19 variants could affect H. pylori eradication rate in patients treated with the proton pump inhibitor (PPI)-based therapy. We therefore performed a meta-analysis of randomized clinical trials (RCTs) to re-evaluate the impact of CYP2C19 variants on PPI-based triple therapy for the above indication. Methods All relevant RCTs in the PubMed, Cochrane Library, EMBASE, Web of Science and two Chinese databases (up to February 2013) were systematically searched, and a pooled analysis was performed with the odds ratio (OR) and 95% confidence interval (CI) by the STATA software. Results Sixteen RCT datasets derived from 3680 patients were included. There was no significant heterogeneity across the data available in this meta-analysis. There were significant differences in that rate between homozygous (HomEMs) and heterozygous (HetEMs) extensive metabolizers (OR 0.724; 95% CI 0.594–0.881), between HomEMs and poor metabolizers (PM) (OR 0.507; 95%CI 0.379–0.679), or between HetEMs and PMs (OR 0.688; 95%CI 0.515–0.920), regardless of the PPI being taken. Furthermore, sub-analysis of individual PPIs was carried out to explore the difference across all the PPIs used. A significantly low rate was seen in HomEMs vs. HetEMs taking either omeprazole (OR 0.329; 95%CI 0.195–0.553) or lansoprazole (OR 0.692; 95%CI 0.485–0.988), and also in HomEMs vs. PMs for omeprazole (OR 0.232; 95%CI 0.105–0.515) or lansoprazole (OR 0.441; 95%CI 0.252–0.771). However, there was no significant difference between HetEMs and PMs taking either one. No significant differences were observed for rabeprazole or esomeprazole across the CYP2C19 genotypes of interest. Conclusions Carriage of CYP2C19 loss-of-function variants is associated with increased H. pylori eradication rate in patients taking PPI-based triple therapies when omeprazole or lansoprazole is chosen. However, there is no a class effect after use of rabeprazole or esomeprazole.